Relation between carotid stiffness, cognitive performance and brain connectivity in a healthy middle-aged population: an observational neurophysiological cohort study with magnetoencephalography. Issue 12 (15th December 2016) - Nieboer, Dagmar; Douw, Linda; van Dijk, Bob W; Heymans, Martijn W; Stam, Cornelis J; Twisk, Jos W R
Abstract : Objective: Impaired blood flow of the carotid artery can result in cognitive impairment, but how these vascular impairments lead to global cognitive disturbances is largely unknown. Problems in functional connectivity between brain areas may be responsible for these widespread effects. Therefore, the aim of this study was to examine the association between carotid stiffness, functional connectivity and cognitive performance in relatively young and healthy adults before clinical vascular pathology occurs. Design: The Amsterdam Growth and Health Longitudinal Study: an observational study. Setting: Participants were included by attending 1 of the 2 selected secondary schools in The Netherlands. Participants: Men (n=110) and women (n=120) aged 41–44 years (42±0.7). Primary and secondary outcome measures: Data were obtained with regard to local carotid stiffness captured measured with the Young's elastic modulus (YEM). All participants underwent a commonly used Dutch intelligence test and resting-state eyes-closed magnetoencephalography (MEG). Five artefact-free epochs were analysed. The phase lag index (PLI) was used as a measure of functional connectivity between all sensors and was assessed in six frequency bands (δ–γ). Results: Carotid stiffness was significantly associated with increased functional connectivity in the α2 band in men (β: 0.287; p=0.008). The same results were found for women in the β band (β: 0.216; p=0.040). Furthermore, carotid stiffness was associated with superior cognitive function in men (β: 0.238; p=0.007). In addition, there was neither a significant association nor a consistent pattern between cognitive function and functional connectivity. Conclusions: The increased connectivity might be a maladaptive phenomenon caused by disinhibition of neurons which may explain the direction of the results. This study suggests that detection of increased (local) carotid stiffness may be promising to identify a disturbance in the organisation of the functional brain network, even before clinical vascular pathology occurs.